2018
DOI: 10.1017/s0022109018000777
|View full text |Cite
|
Sign up to set email alerts
|

Good Volatility, Bad Volatility, and Option Pricing

Abstract: Advances in variance analysis permit the splitting of the total quadratic variation of a jump-diffusion process into upside and downside components. Recent studies establish that this decomposition enhances volatility predictions and highlight the upside/downside variance spread as a driver of the asymmetry in stock price distributions. To appraise the economic gain of this decomposition, we design a new and flexible option pricing model in which the underlying asset price exhibits distinct upside and downside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…Similar to Feunou & Okou (2019) , Hussain (2020) and Lyu et al (2021) , we depart the total volatility into good and bad ones as below: where SGV i,t and SBV i,t are respectively good and bad volatilities of SlogR i,t , RGV i,t and RBV i,t are respectively good and bad volatilities of RlogR i,t for country i at time t.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to Feunou & Okou (2019) , Hussain (2020) and Lyu et al (2021) , we depart the total volatility into good and bad ones as below: where SGV i,t and SBV i,t are respectively good and bad volatilities of SlogR i,t , RGV i,t and RBV i,t are respectively good and bad volatilities of RlogR i,t for country i at time t.…”
Section: Methodsmentioning
confidence: 99%
“…Given the initial time t 0 = 0, expiration T = 1, interest rate r = 0.05, dividend yield q = 0.02, and volatility σ = 0.2, the B-S RNMs m BS t 0 ,T ( j) (j = 1, 2) can be easily calculated using ( 14)- (15). Meanwhile, according to Section 2.2.1, for an underlying asset's price S 0 , numerically computing RNMs via integral expressions (1)-( 2) requires several pairs of "market-traded" options C(T, K) and P(T, K).…”
Section: B Now Return To the Rnms Under B-s Measure M Bsmentioning
confidence: 99%
“…Neri and Schneider [11] investigate the proposition of the density of Buchen-Kelly within the family of maximum entropy densities and find that the densities converge to that of Buchen-Kelly in the sense of relative entropy. Some recent research related to entropy-valuation can also be found in [12,13] and more recently, in [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Bollerslev, Li, and Zhao (2020) show that sorting the individual stocks into portfolios based on their good minus bad volatilities leads to economically and statistically significant differences in the subsequent portfolio returns. Feunou and Okou (2019) show that this decomposition of stock volatility is helpful for improving option pricing performance. Feunou, Jahan-Parvar, and Tédongap (2013) find that good and bad volatility has asymmetric effects on future returns.…”
Section: Introductionmentioning
confidence: 97%